1983
DOI: 10.1289/ehp.835191
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated cytotoxicity expressed by lymphoid cells from rats with asbestos-induced peritoneal mesothelioma towards rat fetal cell.

Abstract: Cell-mediated immunity (CMI) directed towards rat fetal cells was evaluated in Fischer F344 young inbred male rats having asbestos-induced peritoneal mesothelioma. The tumors were induced by exposure to Canadian chrysotile B fibers and the CMI delineated by the injury and destruction brought about to 6- to 10-day-old primary fetal cell cultures by the so-called educated peripheral blood lymphoid-cells (PBLC) obtained from the cancer-bearing rats. A significant cytotoxicity was found to be expressed by the PBLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Chrysotile appears to pose a greater threat than crocidolite. However, IARC recently concluded the evidence to support asbestos-induced stomach cancer to be “limited” ( Straif et al, 2009 ). There is a great deal of inconsistency in the studies of the GIT effects of asbestos, making it difficult to come to any strong conclusions (see Table 3 ).…”
Section: Gastrointestinal Effects Of Asbestosmentioning
confidence: 99%
See 1 more Smart Citation
“…Chrysotile appears to pose a greater threat than crocidolite. However, IARC recently concluded the evidence to support asbestos-induced stomach cancer to be “limited” ( Straif et al, 2009 ). There is a great deal of inconsistency in the studies of the GIT effects of asbestos, making it difficult to come to any strong conclusions (see Table 3 ).…”
Section: Gastrointestinal Effects Of Asbestosmentioning
confidence: 99%
“…In addition, the potential for misdiagnosis of primary diffuse malignant peritoneal mesothelioma in women further complicates the issue ( Kerrigan et al, 2002 ), particularly in older studies that did not use specific markers directed toward serous ovarian carcinoma ( Bollinger et al, 1989 ). Nevertheless, IARC recently concluded that the evidence to date is sufficient to consider asbestos an ovarian carcinogen ( Straif et al, 2009 ). Studies include a cohort of East London factory workers from 1933-1980 who reportedly elevated rates of ovarian cancer ( Newhouse et al, 1985 and a confirmation of excessive ovarian cancer in female gas mask assemblers during World War II ( Wignall & Fox, 1982 ; Acheson et al, 1982 ).…”
Section: Reproductive and Developemental Effects Of Asbestosmentioning
confidence: 99%